Gaming Disorder among Medical College Students during COVID-19 Pandemic Lockdown - Shrestha, M.V.; Manandhar, N.; Sharma, S.C.; Joshi, S.K. (Kathmandu University Medical Journal, 2020)
Background The frequent lockdown in Nepal during COVID-19 pandemic had brought various kinds of complexities such as stress among college students. This situation had created uncertainty of future academic career of undergraduate students in medical colleges. Some previously published literature showed gaming as a coping mechanism against stress. Objective To assess the gaming behavior of Medical college students during lockdown in COVID 19 pandemic. Method A cross-sectional study was conducted during lockdown period of July to August 2020. A total of 412 college students were enrolled. Online Google forms were shared to all the eligible students through email, viber and messenger with the help of class representative. Collected data were analyzed in SPSS version 20.0. Result The prevalence of gaming disorder was 8.5% among 260 internet gaming users. About 69.2% of the participants reported that their gaming behavior had increased due to stress of COVID-19 pandemic. Gender and spending more time online per day showed significant associations with greater scores on the internet gaming disorder. Conclusion During lockdown period of COVID-19 pandemic, the gaming behavior of medical college students has increased.